Reviewing Less—Progressing More - Spiegel, Matthew (Review of Financial Studies, 2012)
Michigan. I want to thank the audience members for their comments and for encouraging me to produce an editorial based on the speech. I also want to thank Professor Hirshleifer for both his comments on an earlier draft and for giving me the opportunity to publish the Review of Financial Studies ’ (RFS) first editorial. I also want to thank Martijn Cremers, Andrew Karolyi, Nancy Nash-Mendez, Paul Tetlock, and Michael Weisbach for their comments. Nothing in here should be construed as representing the views of the Society for Financial Studies or the current editorial board of the RFS. Editorial: Presumably, academic journals exist and publish articles to disseminate new ideas. Somehow that simple goal has been lost. Today, articles appear in print only after a referee is convinced that all other alternative explanations for its results have been ruled out. In reality, no article can exclude every possible alternative, so this is basically an exercise in futility. The criterion for publication should be that once an article crosses some threshold it is good enough to publish. The problem seemingly lies in our inability to say “good enough. ” But this is a problem we can fix. 2 Foreword Because this is an editorial, I want to warn the reader not to expect either the prose or evidence